On the pharmacology of oxidative burst of human neutrophils - Nosáľ, Radomír; Drábiková, Katarína; Jančinová, Viera; Mačičková, Tatiana; Pečivová, Jana; Perečko, Tomáš; Harmatha, Juraj; Šmidrkal, Jan (Physiological research, 2015)
The effect of three therapeutically used drugs and five polyphenolic compounds on the mechanism of oxidative burst was compared in whole blood and isolated neutrophils at cellular and molecular level. In 10 microM concentration, the compounds investigated decreased the oxidative burst of whole blood in the rank order of potency: N-feruloylserotonin (N-f-5HT) > curcumin (CUR) > quercetin (QUER) > arbutin (ARB) > resveratrol (RES) > dithiaden (DIT) > carvedilol (CARV) > brompheniramine (BPA). The ratio between the percentage inhibition of extracellular versus intracellular chemiluminescence (CL) followed the rank order QUER > N-f-5HT > RES > CUR > DIT and is indicative of the positive effect of the compounds tested against oxidative burst of neutrophils, demonstrating suppression of reactive oxygen species extracellularly with minimal alteration of intracellular reactive oxygen species (ROS). Activation of protein kinase C was significantly decreased by DIT, CUR, QUER and N-f-5HT. CARV, DIT, QUER and ARB reduced activated neutrophil myeloperoxidase release more significantly compared with the effect on superoxide anion generation. All compounds tested increased the activity of caspase-3 in cell-free system. It is suggested that other regulatory mechanisms than protein kinase C might participate in the inhibition of neutrophil activation with the compounds tested. Different mechanisms are concerned in controlling the assembly of NADPH oxidase and the regulatory role of calcium ions is suggested. Compounds decreasing the amount of extracellular ROS generation, yet affecting but minimally intracellular ROS generation, are promising for further investigation in vivo.
Keywords: mladý dospělý; reaktivní formy kyslíku; respirační vzplanutí; Adult; Young Adult; lidé středního věku; dospělí; Male; Neutrophils; mužské pohlaví; Respiratory Burst; Middle Aged; Humans; lidé; Reactive Oxygen Species; neutrofily